PROGRAM DALAM PELAKSANAAN TUJUAN PEMBANGUNAN BERKELANJUTAN ( SDGs) DALAM HAL MASALAH PERUBAHAN IKLIM DI INDONESIA - Gindo Leontinus (Jurnal Samudra Geografi, 2022)
This paper specifically discusses Goal 13 related to climate change management where the entire world community is aware of its impact on life now and in the future. Greenhouse gas emissions continue to increase, and levels are currently at 50 percent higher than in 1990. Furthermore, global warming is causing lasting changes to our climate system, and the consequences will be irreversible unless we take action. The establishment of the agenda for the formulation of the Sustainable Development Goals (TPB/SDGs) is a great hope to restore the world as a whole from the bad effects of not obeying environmental ethics and understanding sustainability that affect global climate problems. So that in this paper we will see how the development of programs, policies and solutions that have been implemented related to the goal of dealing with climate change.